An efficient and high-yielding method for extraction and purification of linamarin from Cassava; in vitro biological evaluation. Issue 21 (2nd November 2021) - Samanthi, K. A. U.; Welideniya, Dhanushi T.; Acharige, Anjana Delpe; Samarakoon, Sameera R.; Rathnayaka, Rajitha K.; de Silva, Madhavi; Perera, Shashika S.; Pieris, Colin; Wanninayake, Umayangani K.; Jayathilaka, Adeesha; Karunaratne, Veranja; Amaratunga, G. A. J.; et al.
Abstract: During the last three decades, studies of linamarin extracted from cassava have received increased attention due to the presence of high cyanogenic compounds in these extracts. The methods that are utilized to isolate linamarin are either tedious or use acidic conditions resulting in poor yields. In this study, a novel cryocooled method of extraction has been developed to isolate linamarin from Cassava root peel. Approximately 18 g of linamarin was isolated from 1 kg of fresh Cassava root peel, which is the highest amount reported to date. Linamarin was fully characterized using NMR, IR and LCMS. The anti-cancer properties of pure linamarin and Cassava crude extract were evaluated by a comprehensive cytotoxic assay, using MCF-7, HepG2, NCI H-292, AN3CA and MRC-5 cell lines. The crude extract showed higher cytotoxicity compared to pure linamarin. The results of the biological evaluation are comparable to other reported studies in the literature. Graphical Abstract: